Management of Human Resources Recruitment to Improve BUMDes in Indonesia - Haris, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study is to describe process of Human Resources recruitment management consisting of job analysis, recruitment and selection in BUMDes of Gemblegan, Klaten. This study is qualitative and uses ethnographic design. This study was conducted in the Village of Gemblegan, Klaten. The main subjects of this study were managers of BUMDes of Gemblegan, Klaten. The key informants were Village Chief, Head of Loan & Saving Cooperative (KSP) named “Suka Makmur”. The data of study were collected by interview, observation and documentation. The data were analyzed by using data analysis in site, analysis of structured & unstructured data. Validity of data was tested by using credibility, transferability, conformability and dependability. The results of study indicate that the process of Human Resources recruitment management consisting of job analysis, recruitment and selection in the BUMDes of Gemblegan, Klaten were not implemented well, because all processes were still based on negotiation.